Perbedaan Mekanisme Corporate Governance dan Praktik Manajemen Laba: Studi Komparasi Indeks Syari’ah dan Indeks Konvensional di Bursa Efek Indonesia - Rina Trisnawati (Universitas Islam Indonesia, 2009)
Earning management (EM) exists as an impact of accrual basis. Based on Agency Theory,earning management problems can be reduced by self-control of corporate governance(CG) mechanism. The purpose this study is to analyze the difference of the CG mechanismand EM between those in accordance with syari’ah index (JII) and conventional index(LQ-45). Samples consist of 89 and 39 companies listed in Bursa Efek Jakarta (BEI) from2004 to 2007. The result indicates that the EM practice on the conventional index (0.4027)is higher than syari’ah index (0.2337). The regression analysis shows that the board ofcommissioner size has positive impact on the EM significantly in main model and conventionalindex model, but not in shari’ah model. The managerial ownership has negativeimpact on the EM significantly in conventional index model, but not in syari’ah model.Keywords: earning management, corporate governance, impact, conventional index, syari’ahindex.